Law Enforcement Against the Criminal Act of Gratification in the Form of Sexual Services in Indonesia - Widjaja, Gunawan; Martedjo, Wagiman; Halim , Adriansyah (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
There are several consequences that must be faced, including imprisonment for the perpetrator based on the principle of legality, complicating the evidentiary system, especially in terms of the limits of value that can be classified as gratification so that it can cause a decrease in the markat and dignity of a person, restrictions on the KPK to classify the gratification, and the inability of sexual relations to be assessed as nominal. The purpose of this study is to determine the construction of Indonesian law in regulating criminal acts of gratification in the form of sexual services, and the mechanism of legal protection in Indonesia in the occurrence of criminal acts of gratification in the form of sexual services. The research method used in this study is juridical-normative which uses secondary data, with a statutory regulatory approach and a case approach. The legal sources used include the Criminal Code, the Corruption Law, and other related regulations. The results of the study concluded that the Corruption Law has not explicitly regulated gratification in the form of sexual services, making law enforcement difficult because there is no clear classification. The main obstacles are the principle of legality and the difficulty of proof. Legal reform is needed to expand the definition of gratification as well as clearer technical guidelines and standards of proof, so that the legal system is more responsive to new forms of crime and able to protect from authorities.